From Belief to Business: Cultivating the Impact of Intrinsic Religiosity on Entrepreneurial Intentions via Meaning in Life and Entrepreneurial Self-Efficacy - Sarfraz Zaman; Neelam Bano; Muhammad Zia Aslam (Journal of Islamic Thought and Civilization, 2023)
This study is an attempt to explore the determinants of entrepreneurial intentions based on intrinsic religiosity. Religion plays a vital role in the lives of its followers, and it tends to develop a business mindset among individuals. There is a dearth of studies on the impact of religion on entrepreneurial intentions, especially in the Pakistani context. The study's novelty is to explore this less-discussed relation between religion and inclination towards business by using social cognitive theory. This relationship is mediated by two variables, which are meaning in life and self-efficacy. Both mediators are antecedents of intrinsic religiosity and precedents of entrepreneurial intentions. For this purpose, the data was collected from 410 postgraduate students of three Pakistani universities, who are studying in their final semesters. Furthermore, this study employed WarpPLS to analyze the data. The findings of the paper revealed that religion plays an important role in developing entrepreneurial intentions. This research has theoretical contributions as well as managerial implications. Theoretically, it contributes to the literature of social cognitive theory and adds knowledge to the religious dimension. Practically, it guides government and institutional managers that for the development of entrepreneurial intentions among individuals they can also consider the religious curriculum and practices for developing their business.